CHANGES OF WEED COMMUNITIES IN SECONDARY SUCCESSION ON RICE FIELD AREA WITH DIFFERENT WATER PUDDLE - Harsoyo Purnomo (Bioma : Jurnal Ilmiah Biologi, 2011)
The composition of weed communities in rice fields is always changing from time to time, or having a secondary succession. What is the pattern of change, and what factors affecting it needs to study as the cornerstone of efforts to eliminate or mini-mize the competition between weeds and crops through to appropriate controls. The study aims to determine the pattern of changes in weed community compositi- on, the factors that affecting and determine the right moment for its control. Research done in the area Mijen, Semarang. Three each plot measuring 100 m2 each chosen selectively according to the level of water puddle, namely the wet rice field (irrigated rice fields), dry rice field (rainfed rice field), and moderate rice field (me-sic). Into each plot was placed 15 permanent circular quadrat frames with the size of one square meter randomly. Observations carried out every two weeks once, by calculating the density species. Data were analyzed and interpretation with Shannon -Wiener diversity index, and PIE (Probability of Interspecific Encounter). The results showed the general community of progressive change, and is rhythmic. In the wet plot there are 20 species of weeds, the mesic plot is 29 species, and dry plot 38 species. Diversity index and the highest PIE being found on the plot mesic. At week 4, the emergence of weeds in wet plots reached 90.69%, the moderate plot?é?á (mesic) 68.77%, and the dry plot 58.40% of the total individual. The conclusion is, changes in weed communities affected by the level of water pud-dle. Higher levels of the water puddle, the fewer the number of its kind, and the faster the rate of emergence. Continuous inundation can prevent the emergence of some weed species. Most appropriate for the control (weeding) weed is between weeks 4 and weeks 6 after transplanting. Key words: rice field area, secondary succession, weed communities, water puddles, diversity.